Negotiating Piety and Radicalism: A Study Among Muslim Youth in Pekanbaru, Indonesia - Khotimah, Khotimah; Rosidi, Imron (SCAD Independent, 2020)
Muslim youth in Pekanbaru currently interacts with different culture and tradition. They actively consume modern values spread by global media from different countries. In Muslim societies like Pekanbaru, the rise of modernity and globalization brings multiple impacts on them. One of them is that it supports the growth of piety or religiosity both in the private and public sphere among young Muslims. However, some people may indicate that this piety is a potential or same as radicalism. Radicalism and piety are two complicated terms among young Muslims in this town. As a result, this raises a question on how these Muslim youth understand and practice radicalism and piety. This article argued that, as the impact of globalization and modernity, piety was blended with capitalism and other non-Islamic ideologies. As a result, this article found that, first, Muslim youth in Pekanbaru were negotiating their piety and radicalism with non-Islamic ideologies such as modernity, capitalism, and so forth. Secondly, they could not be labeled into a single term like pious or radical. This is because they were still in the process of negotiation between piety and radicalism.